Dynamic footprints of α-synucleinopathic mice recorded by CatWalk gait analysis - Timotius, Ivanna; Canneva, Fabio; Minakaki, Georgia; Pasluosta, Cristian Federico; Moceri, Sandra; Casadei, Nicolas; Riess, Olaf; Winkler, Jürgen; Klucken, Jochen; von Hörsten, Stephan; Eskofier, Björn (Data in Brief, 2018)
Characterizing gait is important in the study of movement disorders, also in clinical mouse models. Gait data are therefore necessary for the development of gait analysis methods and the study of diseases. This article presents gait data of two α-synucleinopathic transgenic mouse models and their non-transgenic littermate, backcrossed into the C57BL/6N genetic background. The animal gait was recorded using CatWalk system, which provides the information for each run about the paw positions, paw print sizes, and paw intensities as a function of time or video frame. A total of 90 run data files are provided in this article.
Keywords: Data; gait analysis; CatWalk system; Parkinson's disease; alpha-synuclein transgenic.